Clinical study on management of venous ulcer - Voruganti, Mohan Rao; Mohammed, Nooruddin; Tummala, Sushmitha (International Surgery Journal, 2022)
Background: Venous ulcer is the most common ulcer affecting the lower limbs, usually associated with varicose veins. They are diagnosed by their location, morphology, skin changes, and association with venous insufficiency. They are complicated with local scarring, ankylosis of ankle joint, and occasionally malignancy. Diagnosis is confirmed by venous duplex imaging. They significantly reduce quality of life due to pain, and reduced mobility leading to loss of income and social isolation. Cost estimates put them at upwards of 2% of national resources. Recurrence is high with conservative treatment. Surgery addressing venous valvular insufficiency plays a major role. Objectives of current study was to assess the role of conservative treatment and surgical management of venous ulcers. Methods: A cross-sectional study of 80 patients in the period 2019 -2020 at a tertiary care center. Results: 84% of the patients were male with maximum patients in the 6th decade. 67% were overweight. Conservative treatment was done in 22% of cases and surgery for 78%. Flush ligation and venous stripping with perforator ligation was the most common surgery done. 89% of the patients achieved healing by the end of 3 months, and 7% by the end of 6 months. Wound healing time in surgical vs conservatively was 8.3 and 10.4 weeks respectively. Conclusions: Correction of underlying venous insufficiency is the main stay of the treatment. Surgery gives best results with long term benefits.